158k views
3 votes
Solve the equation for the given variable.
-2 (x + 6) = 8

User Robasaurus
by
5.0k points

2 Answers

1 vote
Answer:
x=10

STEP BY STEP EXPLANATION:

1. distribute -2(x+6) to get a total of -2x+-12
2. Add 12 on both sides and you’re left with -2x=20
3. Now you divide -2 on both sides.., now you’re left with x=10
User Fran Sevillano
by
5.6k points
3 votes

Answer:

x = -10

Explanation:

-2 (x + 6) = 8

-2x + -12 = 8

+12 +12

-2x = 20

÷ -2 ÷ -2

x = -10

User Muralikrishna G S
by
5.0k points